2019
DOI: 10.1177/1744806919859723
|View full text |Cite
|
Sign up to set email alerts
|

Spinal 5-HT3 receptor contributes to somatic hyperalgesia induced by sub-chronic stress

Abstract: Stress facilitates pain perception and sensitizes pain pathways, but the underlying mechanism is still unclear. The purpose of this study was to investigate whether the activation of 5-hydroxytryptamine (5-HT) subtype-3 receptor in the spinal cord contributes to somatic hyperalgesia induced by repeated three-day forced swim in the estradiol replacement rats after ovariectomy. Somatic sensitivity was assessed by thermal withdrawal latency to radiant heat and mechanical withdrawal threshold to von Frey filaments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Our recent studies also provided evidence for 5-HT 3 receptors involved in somatic pain, an obvious symptom of FMS [127]. Specifically, we established an FMS model with three-day forced swim stress in female rats and investigated the role of the spinal 5-HT 3 receptors in somatic pain induced by stress [127]. We found that the expression of 5-HT 3 receptors in L4-5 spinal dorsal horn upregulated with the occurrence of pain and blocking 5-HT 3 receptors by intrathecal administration of Y25130 reversed this process, providing a possible mechanism of 5-HT 3 receptor antagonists applied in chronic pain without local tissue pathology [127].…”
Section: -Ht 3 Receptorssupporting
confidence: 52%
See 2 more Smart Citations
“…Our recent studies also provided evidence for 5-HT 3 receptors involved in somatic pain, an obvious symptom of FMS [127]. Specifically, we established an FMS model with three-day forced swim stress in female rats and investigated the role of the spinal 5-HT 3 receptors in somatic pain induced by stress [127]. We found that the expression of 5-HT 3 receptors in L4-5 spinal dorsal horn upregulated with the occurrence of pain and blocking 5-HT 3 receptors by intrathecal administration of Y25130 reversed this process, providing a possible mechanism of 5-HT 3 receptor antagonists applied in chronic pain without local tissue pathology [127].…”
Section: -Ht 3 Receptorssupporting
confidence: 52%
“…5-HT 3 receptor antagonists dolasetron and tropisetron have been assessed for efficacy in FMS patients [125,126]. Our recent studies also provided evidence for 5-HT 3 receptors involved in somatic pain, an obvious symptom of FMS [127]. Specifically, we established an FMS model with three-day forced swim stress in female rats and investigated the role of the spinal 5-HT 3 receptors in somatic pain induced by stress [127].…”
Section: -Ht 3 Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NMDA receptor antagonist 2-amino-5-phosphonovaleric acid (APV, 30 nmol in 10 μl, Sigma, St. Louis, MO, USA) or 5-HT 3 receptor antagonist Y-25130 (30 fmol in 10 ul, Tocris, Bioscience, Bristol, UK ) was then administered at 30 min before CFA injection and each FS. The doses of drugs were determined by previous studies [ 13 , 14 ] and our preliminary experiments. Intrathecal injection of saline was used for vehicle control.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, interpretation of immobility behaviors as depression-like behaviors is controversial [ 179 , 180 ]; however, FS is the useful model for studying the basis for stress-induced hyperalgesia, since FS (10–20 min/day) could consistently increase nociceptive responses in the animals. For example, FS for 2–3 days causes hyperalgesia in the hindpaw, increased neural activities in the lumbar dorsal horn [ 181 , 182 ] and in the supra-spinal areas [ 183 , 184 ].…”
Section: Preclinical Models For Psychological Stress and Deep Craniofacial Pain ( Table 1 )mentioning
confidence: 99%